High-pressure phase equilibria of systems carbon dioxide + n-eicosane and propane + n-eicosane - Rodriguez Reartes, Sabrina Belen (2009)
In this work we investigated the phase equilibrium behavior of the binary asymmetric systems propane (C3) + n-eicosane (C20) and carbon dioxide (CO2) + n-eicosane (C20). We used a variable-volume view cell for obtaining fluid-fluid equilibrium (FFE), solid-fluid equilibrium (SFE) and solid-fluid-fluid equilibrium (SFFE) experimental data. We modeled the phase equilibria of both systems using the Peng-Robinson Equation of State for describing the fluid phases and an expression for the fugacity of pure solid n-eicosane with parameters fit to reproduce the pure n-eicosane melting line. We performed the phase equilibrium calculations by implementing path-following methods for tracking entire solid-fluid (SF) and solid-fluid-fluid (SFF) equilibrium curves for binary asymmetric mixtures. This made it possible to obtain complete isoplethic lines or complete three-phase equilibrium lines in single runs. Although the model is relatively simple, it is able to grasp the complex observed behavior for the systems studied here. © 2009 Elsevier B.V. All rights reserved.